Understanding the Value of Creative Dance by Fostering Empathy: A Collaborative Project with a Malaysian Kindergarten - Tan Chai Chen (Wacana Seni Journal of Arts Discourse, 2024)
In Malaysian kindergartens, the dance show is one of the highlights of the annual school concert. Rehearsals for the dance show are teacher-oriented, where teachers teach dance to children through demonstrations. In 2008, I was hired as a dance teacher and consultant by a kindergarten in Shah Alam to produce annual dance shows. Over 10 years, I began to see cracks in teacher-oriented instruction. It does not allow children to move and express themselves creatively. It deprives them of holistic growth opportunities. In 2018 and 2019, I proposed that the kindergarten shift from teacher-oriented instruction to creative dance through a collaboration project. Shifting the method of teaching dance means changing the ethos and culture of a kindergarten community. It was a process that involved communication and discussion with the principal, administrators, teachers, and parents about a change in expectations—how we value dance and work together to produce a dance show. Ultimately, we wanted to provide children with a better and healthier dance learning experience. This could be achieved through building a consensus on dance value in the kindergarten community. This article discusses how I managed to create an understanding of the value of creative dance by fostering empathy in the kindergarten community. In short, the consensus building of the value of dance was achieved through four approaches: (1) understand the needs of the principal and dance teachers through empathic listening, (2) foster empathy for children among dance teachers through embodiment and reflection activities, (3) foster empathy among class teachers and administrators to provide a pleasant and healthier dance learning experience, and (4) assign children as the agents in encouraging the empathic participation of their parents in their creative dance learning.